2009
DOI: 10.1182/blood-2008-08-176123
|View full text |Cite
|
Sign up to set email alerts
|

Cytohesin-1 controls the activation of RhoA and modulates integrin-dependent adhesion and migration of dendritic cells

Abstract: Adhesion and motility of mammalian leukocytes are essential requirements for innate and adaptive immune defense mechanisms. We show here that the guanine nucleotide exchange factor cytohesin-1, which had previously been demonstrated to be an important component of beta-2 integrin activation in lymphocytes, regulates the activation of the small GTPase RhoA in primary dendritic IntroductionIntegrin-mediated adhesion is an essential function of most metazoan cells, and plays a key role in, for example, organ dev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
63
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 56 publications
(70 citation statements)
references
References 47 publications
6
63
0
Order By: Relevance
“…12 Furthermore, the second CCR7 ligand CCL19 was recently found to induce a general b2-integrin activation epitope on mature DCs. 18 Therefore, we investigated whether CCL21 was responsible for the upregulation of the LFA-1 activation epitope NKI-L16 on human DCs.…”
Section: Ccl21 Strongly Binds To Dcs and Induces Active Lfa-1mentioning
confidence: 99%
See 1 more Smart Citation
“…12 Furthermore, the second CCR7 ligand CCL19 was recently found to induce a general b2-integrin activation epitope on mature DCs. 18 Therefore, we investigated whether CCL21 was responsible for the upregulation of the LFA-1 activation epitope NKI-L16 on human DCs.…”
Section: Ccl21 Strongly Binds To Dcs and Induces Active Lfa-1mentioning
confidence: 99%
“…However, the contribution of integrins in DC (trans-) migration remains controversial as it was shown that knockdown of all integrins in murine DCs did not impair the migration of DCs from the periphery to the secondary lymphoid organs. 38 Nevertheless, Quast et al 18 have shown that although phenotypically similar, migration of integrin-null and integrin-bearing murine DCs within the interstitium is molecularly distinct. While integrin-bearing DCs require cytohesin-1 and RhoA signaling, integrin-null DCs use a cytohesin-1-independent, RhoA-dependent signaling pathway for migration.…”
Section: Ccl21 Strongly Binds To Dcs and Induces Active Lfa-1mentioning
confidence: 99%
“…Furthermore, the type of diffusion of LFA-1 subpopulations did not seem to change upon differentiation. Therefore, it is tempting to believe that imDCs are still potentially active and might be able to switch to an active state where LFA-1 mediated adhesion is required, which is in line with recent studies on the role of LFA-1 in DCs [15,16,18,227].…”
Section: Discussionmentioning
confidence: 66%
“…On monocytes, LFA-1 plays a similar role [12,13]. Upon differentiation of monocytes towards immature DCs [14], LFA-1 functionality is downregulated [3], although recent findings suggest that LFA-1 does play a role during certain stages of the DC life cycle [15][16][17][18]. In addition, LFA-1 on lymphocytes acts as a co-receptor by binding to ICAM-1 on mature DCs during the immunological synapse [19,3].…”
Section: Lfa-1 In the Immune Systemmentioning
confidence: 99%
See 1 more Smart Citation